2016
DOI: 10.1016/j.biopsycho.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Rapid attentional selection processes operate independently and in parallel for multiple targets

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In Experiment 2 , we found that blue cues elicited standard validity effects in the positive search task but non-significant validity effects in the negative search task consistent with previous evidence for the flexibility of top-down control in visual search for specific colors (e.g., Grubert & Eimer, 2016 ; Lien et al, 2010 ). Furthermore, our results indicate that cues selectively captured attention depending on whether they carried a target-matching feature.…”
Section: Methodssupporting
confidence: 87%
“…In Experiment 2 , we found that blue cues elicited standard validity effects in the positive search task but non-significant validity effects in the negative search task consistent with previous evidence for the flexibility of top-down control in visual search for specific colors (e.g., Grubert & Eimer, 2016 ; Lien et al, 2010 ). Furthermore, our results indicate that cues selectively captured attention depending on whether they carried a target-matching feature.…”
Section: Methodssupporting
confidence: 87%
“…This problem can be overcome by presenting one of these targets on the vertical meridian (above or below fixation). Because vertical targets do not elicit N2pc components, the N2pc will exclusively reflect the selection of the horizontal target, independently of any additional attentional processing of the vertical target object (e.g., Eimer & Grubert, 2014;Eimer, Kiss, & Nicholas, 2011;Hickey, Di Lollo, & McDonald, 2009;Hickey, McDonald, & Theeuwes, 2006;Woodman, & Luck, 1999;Eimer & Grubert, 2014;Grubert & Eimer, 2015, 2016aJenkins, Grubert, & Eimer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, alternative accounts are possible. For instance, it is possible that the attentional processes involved in the comparison of two stimuli take longer than processes involved in the identification of a single stimulus (see Grubert & Eimer, 2016a, Experiment 1, for similar findings). More research is needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 87%
“…These predictions also rely on the assumption that the response-irrelevant shapes surrounding the target lines are attentionally processed. That is, a single focus of attention is either shifted rapidly between the two relevant target locations or is expanded to include both target locations for parallel processing (Eimer & Grubert, 2014;Grubert & Eimer, 2016a). For instance, the attentional focus may take on the shape of an ellipse including the two lateral positions and (at least part of) the surrounding shapes (e.g., Pan & Eriksen, 1993).…”
Section: Methodsmentioning
confidence: 99%